16-6y=-9(7y-8)

Simple and best practice solution for 16-6y=-9(7y-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16-6y=-9(7y-8) equation:


Simplifying
16 + -6y = -9(7y + -8)

Reorder the terms:
16 + -6y = -9(-8 + 7y)
16 + -6y = (-8 * -9 + 7y * -9)
16 + -6y = (72 + -63y)

Solving
16 + -6y = 72 + -63y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '63y' to each side of the equation.
16 + -6y + 63y = 72 + -63y + 63y

Combine like terms: -6y + 63y = 57y
16 + 57y = 72 + -63y + 63y

Combine like terms: -63y + 63y = 0
16 + 57y = 72 + 0
16 + 57y = 72

Add '-16' to each side of the equation.
16 + -16 + 57y = 72 + -16

Combine like terms: 16 + -16 = 0
0 + 57y = 72 + -16
57y = 72 + -16

Combine like terms: 72 + -16 = 56
57y = 56

Divide each side by '57'.
y = 0.9824561404

Simplifying
y = 0.9824561404

See similar equations:

| P(2)=-0.1x^5+3.8x^4+5000 | | 8x-6(2x-7)=-23 | | 8m+6n-3m+7n= | | -b^2+2b-6=0 | | 4y=7x^2-5 | | 4(2x+5)-7(x-3)= | | 8s-19=-25+6s | | 8(9+y)=7(y-3) | | sin(i)=0.4 | | 3t-3=-12+2t | | 2+2r=3-4r | | 3(n+4)=n+4 | | 14x+69=x | | 5z+3z=6z-7 | | x^3-4x^2-207x+630=0 | | 5x=88 | | 5x+2y+2z=7 | | 4(4x-8)-5=(x-3)+35 | | r+9.3=-0.5 | | (X+1)+(3x+1)+(x+1)=180 | | P(x)=-0.1x^5+3.8x^4+5000 | | 7-x=-2x-5 | | 0.4+1.5=2.2-15x | | 2n^2+2n-42=0 | | 5(3+5x)-1=89 | | 10-2a+4=32 | | 3=-4n+3n | | 2(j-3)=9(6-3j)+10j | | 9x^2+26x+17=0 | | 3p+6=2p+10 | | 20(y+2)=4y+5 | | 2j-6=54-27j+10j |

Equations solver categories